Criminal Liability for Victims of Robbery Who Engage in Emergency Self-Defense - Dewa Ayu Dwi Purnamasari; A. A. Ngurah Oka Yudistira Darmadi (Transpublika Publisher, 2025)
The purpose of this writing is to examine criminal acts that can be classified under forced defense and to analyze the form of criminal liability for victims of robbery who defend themselves in emergency situations. This research applies a normative legal approach, utilizing the study and analysis of literature sources in accordance with primary, secondary, and tertiary legal materials, and employing conceptual and legal approach methods. The results of this writing explain that criminal acts can be excluded from punishment if they meet the elements of forced defense as stipulated in Article 49 of the Criminal Code. The victim of the crime of robbery (begal) who defends themselves in an emergency cannot be convicted if the action is carried out proportionally, as a reaction to a real threat to self, honor, or property. The recognition of forced defense as a reason for criminal expungement provides legal protection for victims of crime who are forced to defend themselves. This encourages law enforcement officials to consider aspects of justice, proportionality, and the context of the event in the criminal justice process.